Health informatics : digital health service delivery, the future is now! : selected papers from the 21st Australian National Health Informatics Conference (HIC 2013). - Grain, Heather; Schaper, Louise K. (Studies in health technology and informatics, 2013)
Healthcare systems around the world are going through immense changes as innovative approaches to healthcare delivery are adopted to reduce cost and improve quality of care. Health informatics professionals are increasingly required to support these changes, and innovation, learning from experience and sharing ideas are essential to delivering the promises of e-health. This book presents the proceedings of the 21st Australian National Health Informatics Conference (HIC 2013), held in Adelaide, Australia in July 2013. The theme of HIC 2013 is 'Digital Health Service Delivery - the Future is Now!